Hazardous waste management in Malaysia : Current situation, possible management strategy, and treatment approaches - Abdullah, Abdul Hamid; Mohd. Yusoff, Mohd. Rashid (1989)
Malaysia has embarked seriously on identifying the possible toxic and hazardous waste in Malaysia. In 1987, the Department of Environment concluded that approximately 380 000 cubic meters of the waste was generated and about 600 000 containers of the waste are disposed yearly. It was found that about 647 out of 747 industries generated the waste. Currently, very little treatment ; recovery and Treatment Plant is essential. Several sites were indicated for the construction of the plant but unfortunately one of situation and the possible treatment approaches that can be considered in Malaysia.